Development of an Android-Based QR Code Information System for Offline-First Palm Oil Harvest Recording in Plantations - Bintang Permata Hati Simanjuntak; Raden Aris Sugianto; Andi Prayogi (Academic Bright Collaboration, 2026)
Purpose – Manual palm oil harvest recording at remote plantations often causes transcription errors, duplicate records, delayed reporting, and difficulties in implementing fully online data collection because of unstable Internet connectivity. This study aimed to design and develop an Android-based palm oil harvest recording information system using Quick Response (QR) Code identification and an offline-first data architecture. Methods – This study employed a Research and Development approach using the Rapid Application Development model. Data were collected through field observations, interviews with five foremen and one administrative staff member, documentation reviews, and functional system testing. The application was developed using Android Studio and Flutter, with SQLite for local offline storage and Firebase Cloud Firestore for online data synchronization. Findings – The developed system enables QR Code-based worker identification, harvest data input, offline data storage, automatic synchronization, digital signature validation, activity-log monitoring, and report export. Black-box testing of seven functional scenarios showed that all tested features operated correctly in both offline and online conditions. Research implications – The findings indicate that an offline-first mobile architecture can support harvest recording in plantation areas with limited connectivity and low-cost devices. However, the system was tested in one plantation environment; therefore, broader implementation requires further multisite evaluation. Originality – This study contributes by integrating QR Code identification, SQLite-based offline persistence, Firebase synchronization, and Android-based field reporting into a single harvest recording system for remote palm oil plantation operations.